Unravel parking difficulty via relative chain code algorithm / Chan Huey Min - Chan , Huey Min (2005)
Searching for parking space is a familiar challenge to city-dwellers everyday. With the increasing numbers of vehicles, not only the roads are congested, it is also difficult to find parking space everywhere especially in shopping complexes. Unravel Parking Difficulty via Relative Chain Code Algorithm is a parking system which will help vehicles' owner to maneuver their means of transportation without the need of scrupulously locating a vacant parking space in the parking bay. This system will allow drivers to quickly locate an available parking space without hassle, thus they can save time from searching for vacant space. This project focuses on the image processing stage, where it will go through from the process of detecting empty space, character recognition, updating the database to notifying drives about available car park.